Productivity of sodic soils can be enhanced through the use of salt tolerant rice varieties and proper agronomic practices - Singh, Y.P.; Mishra, V.K.; Singh, Sudhanshu; Sharma, D.K.; Singh, D.; Singh, U.S.; Singh, R.K.; Haefele, S.M.; Ismail, Abdelbagi M. (Elsevier, 2016)
Regaining the agricultural potential of sodic soils in the Indo-Gangetic plains necessitates the development of suitable salt tolerant rice varieties to provide an entry for other affordable agronomic and soil manipulation measures. Thus selection of high yielding rice varieties across a range of sodic soils is central. Evaluation of breeding lines through on-station and on-farm farmers’ participatory varietal selection (FPVS) resulted in the identification of a short duration (110–115 days), high yielding and disease resistant salt-tolerant rice genotype ‘CSR-89IR-8’, which was later released as ‘CSR43’ in 2011. Several agronomic traits coupled with good grain quality and market value contributed to commercialization and quick adoption of this variety in the sodic areas of the Indo-Gangetic plains of eastern India. Management practices requiredfor riceproductioninsalt affectedsoils are evidentlydifferentfromthose innormal soils and practices for a short duration salt tolerant variety differ from those for medium to long duration varieties. Experiments were conducted atthe Indian Council of Agricultural Research-Central Soil Salinity Research Institute (ICAR-CSSRI), Regional Research Station, Lucknow, Uttar Pradesh, India during 2011 and 2013 wet seasons, to test the hypothesis that combining matching management practices (Mmp) with an improved genotype would enhance productivity and profitability of rice in sodic soils. Mmp were developed on-station by optimizing existing best management practices (Bmp) recommended for the region to match the requirements of CSR43. The results revealed thattransplanting 4 seedlings hill−1 at a spacing of 15 × 20 cm produced significantly higher yield over other treatments. The highest additional net gain was US$ 3.3 at 90 kg ha−1 N, and the lowest was US$ 0.4 at 150 kg ha−1 N. Above 150 kg ha−1, the additional net gain became negative, indicating decreasing returns from additional N. Hence, 150 kg N ha−1 was considered the economic optimum N application rate for CSR43 in these sodic soils. Using 150–60–40-25 kg N–P2O5–K2O–ZnSO4·7H2O ha−1 in farmers’ fields grown to CSR43 produced an average of 5.5 t ha−1 grain. The results of on-farm evaluation trials of CSR43 showed that matching management practices (Mmp) increased yield by 8% over existing best management practices (Bmp) recommended by ICAR-CSSRI for sodic soils and by 16% over framers’ management practices; however, combining Mmp with CSR43 resulted in 35% higher yields over farmers’ current varieties and management. This approach of combining cost effective crop and nutrient management options and a salt-tolerant variety can maximize the productivity and profitability of sodic soils in the alluvial Indo-Gangetic plains and in neighboring salt-affected areas of the Ganges mega delta in South Asia